Protein phosphatase PP2A regulates microtubule orientation and dendrite pruning in Drosophila. (18th March 2020) - Rui, Menglong; Ng, Kay Siong; Tang, Quan; Bu, Shufeng; Yu, Fengwei
Abstract: Pruning that selectively eliminates inappropriate projections is crucial for sculpting neural circuits during development. During Drosophila metamorphosis, ddaC sensory neurons undergo dendrite‐specific pruning in response to the steroid hormone ecdysone. However, the understanding of the molecular mechanisms underlying dendrite pruning remains incomplete. Here, we show that protein phosphatase 2A (PP2A) is required for dendrite pruning. The catalytic (Microtubule star/Mts), scaffolding (PP2A‐29B), and two regulatory subunits (Widerborst/Wdb and Twins/Tws) play important roles in dendrite pruning. Functional analyses indicate that PP2A, via Wdb, facilitates the expression of Sox14 and Mical prior to dendrite pruning. Furthermore, PP2A, via Tws, governs the minus‐end‐out orientation of microtubules (MTs) in the dendrites. Moreover, the levels of Klp10A, a MT depolymerase, increase when PP2A is compromised. Attenuation of Klp10A fully rescues the MT orientation defects in mts or pp2a‐29b RNAi ddaC neurons, suggesting that PP2A governs dendritic MT orientation by suppressing Klp10A levels and/or function. Taken together, this study sheds light on a novel function of PP2A in regulating dendrite pruning and dendritic MT polarity in sensory neurons. Synopsis: Protein phosphatase PP2A plays a crucial role in dendrite pruning in Drosophila sensory neurons. PP2A acts via two regulatory subunits Widerborst and Twins to mediate ecdysone signaling and to control microtubule orientation in dendrites. Protein phosphatase PP2A regulates dendrite pruning through two distinct regulatory subunits, Widerborst/Wdb and Twins/Tws. PP2A, via one regulatory subunit Wdb, facilitates the expression of Sox14 and Mical, two important downstream targets of ecdysone signaling, which are required for dendrite pruning. PP2A, via the other regulatory subunit Tws, regulates dendritic microtubule orientation and thereby dendrite pruning. PP2A governs dendritic MT orientation by suppressing Klp10A levels and/or function. Abstract : Protein phosphatase PP2A plays a crucial role in dendrite pruning in Drosophila sensory neurons. PP2A acts via two regulatory subunits Widerborst and Twins to mediate ecdysone signaling and to control microtubule orientation in dendrites.